A Retrospective Review Comparing the Safety and Efficacy of 120 Versus 160 Applications of Selective Laser Trabeculoplasty. Issue 1 (January 2018) - Wong, Cliff; Tao, Lingwei W.; Skalicky, Simon E.
Abstract : Purpose: To compare the effectiveness and safety of 120 applications versus 160 applications of selective laser trabeculoplasty (SLT) at reducing intraocular pressure (IOP) from baseline in glaucoma patients over a 1-year period. Methods: A retrospective chart review was conducted, comprising 376 eyes from 199 patients who underwent SLT treatment performed by the same glaucoma subspecialist from 2014 to 2015. Data were obtained on patients' clinical features, management, and outcomes. Patients were treated with either 120 applications or 160 applications of SLT per 360 degrees of trabecular meshwork over 2 sessions. Statistical analyses were performed comparing baseline IOP with IOP at 6 weeks and 1-year follow-up after completion of treatment. The incidence and severity of transient IOP rises immediately post-SLT was also recorded. Results: Both SLT regimes were effective at reducing IOP. Univariate t tests showed that the 160 applications group had significantly greater mean reduction of IOP from baseline at both 6 weeks (4.6 vs. 3.6 mm Hg, P =0.015) and 1-year time points (4.1 vs. 2.8 mm Hg, P =0.019). However, when multivariate analyses were used to account for the effects of clustering and include other covariates such as age, baseline IOP, history of previous SLT there was no significant difference between success rates of the 2 treatment groups at either time points. Higher baseline IOP was associated with greater IOP reduction at 6 weeks ( P <0.001) and 1 year ( P <0.001) for both treatment groups. There was no statistical difference in incidence and severity of IOP spikes at 1-hour post-SLT between the 2 treatment groups. Conclusions: SLT produces a significant IOP-lowering effect and treatment with 160 applications per 360 degrees may be more effective than 120 applications per 360 degrees. Furthermore, 160 applications of SLT does not increase the risk of transient IOP spikes.